Delta-opioid-receptor-mediated inhibition of adenylate cyclase is transduced specifically by the guanine-nucleotide-binding protein Gi2. - McKenzie, F R (1990)
Mouse neuroblastoma x rat glioma hybrid cells (NG108-15) express an opioid receptor of the delta subclass which both stimulates high-affinity GTPase activity and inhibits adenylate cyclase by interacting with a pertussis-toxin-sensitive guanine-nucleotide-binding protein(s) (G-protein). Four such G-proteins have now been identified without photoreceptor-containing tissues. We have generated anti-peptide antisera against synthetic peptides which correspond to the C-terminal decapeptides of the alpha-subunit of each of these G-proteins and also to the stimulatory G-protein of the adenylate cyclase cascade (Gs). Using these antisera, we demonstrate the expression of three pertussis-toxin-sensitive G-proteins in these cells, which correspond to the products of the Gi2, Gi3 and Go genes, as well as Gs. Gi1, however, is not expressed in detectable amounts. IgG fractions from each of these antisera and from normal rabbit serum were used to attempt to interfere with the interaction of the opioid receptor with the G-protein system by assessing ligand stimulation of high-affinity GTPase activity, inhibition of adenylate cyclase activity and conversion of the receptor to a state which displays reduced affinity for agonists. The IgG fraction from the antiserum (AS7) which specifically identifies Gi2 in these cells attenuated the effects of the opioid receptor. This effect was complete and was not mimicked by any of the other antisera. We conclude that the delta-opioid receptor of these cells interacts directly and specifically with Gi2 to cause inhibition of adenylate cyclase, and that Gi2 represents the true Gi of the adenylate cyclase cascade. The ability to measure alterations in agonist affinity for receptors following the use of specific antisera against a range of G-proteins implies that such techniques should be applicable to investigations of the molecular identity of the G-protein(s) which interacts with any receptor.